(untitled) (Unilorin Journal of Lifelong Education, 2023)
Today, technology is the mainstay of any societal development and mathematics has been recognised as the bedrock of technology and sciences. This implies that the mathematical development of every child cannot be ignored at basic education level. Despite the importance of mathematics, pupils’ performance in basic mathematics has not been encouraging. This study examines locus of control as a correlate of pupils’ academic performance in mathematics. Correlational survey research design was adopted for this study. The population comprises all Basic Six pupils in Lagos Central Senatorial District from which 375 pupils were selected using multi-stage sampling technique. Pupils’ Locus of Control Scale (PLOCS) and Mathematics Performance Test (MPT) were the instruments adapted and used to gather data for this research. Experts in Social Sciences Education and Sciences Education Departments were given the instruments for validation. The instruments were subjected to test-re-test method of reliability and were found to have reliability coefficient of 0.74 and 0.80 respectively. The research questions were answered using percentage and summated mean rating while Pearson Product Moment Correlation was used to test the hypothesis at 0.05 level of significance. The findings revealed that there was a positive significant relationship between locus of control and pupils’ academic performance in mathematics. Among the recommendations made was that; Since pupils with external locus of control performed better in Mathematics, teachers should make reinforcement (praise, token gifts etc.) an aspect of learning whenever the pupils perform outstandingly in their academic work so as to prompt them to do better.